Design of API Gateway as Middleware on Platform as a Service - Dita Oktaria; Joel Andrew M. K. Ginting; Maman Abdurohman; Rahmat Yasirandi (School of Computing, Telkom University, 2021)
The process of building a platform is a process that consists of various stages, there is a focus of work and requires different preparation, but until now there has been no awareness in utilizing data and information sources that have been available to be used as a basis for developing or creating a platform that is able to improve quality a system of integrity. For this reason, a Platform as a Service (PaaS) architecture was built which provides application development services to process data and information obtained from practicum activities during the lecture period based on cloud computing using the Service Oriented Architectural (SOA) method. The API gateway is used as middleware system. The results of the implementation and analysis carried out prove that the architecture using the API gateway as a built-in middleware can be considered to develop the Telkom University lab service system. Although there are adjustments to resources and needs, but the purpose of this architectural development has generally been realized. From the results of tests performed on a platform architecture that uses a gateway API, it produces RTT 2.081 seconds, 45 MB memory, and 8% CPU for each user in 100 users.